Factors that Differentially Affect Daytime and Nighttime Sleep in Drosophila melanogaster - Ishimoto, Hiroshi; Lark, Arianna R.; Kitamoto, Toshihiro (Frontiers in Neurology, 2012)
Rest in the fruit fly Drosophila melanogaster has key characteristics of mammalian sleep and is thus considered as a fly version of sleep. Drosophila sleep has been studied extensively, with the aim of gaining fundamental insights into the evolutionarily conserved functions of sleep as well as the mechanisms that regulate it. An interesting question that has not yet been addressed is whether fly sleep can be classified into distinct sleep types, each having particular biological roles—like REM and non-REM sleep in birds and mammals. Typically, Drosophila sleep displays a bimodal pattern, consisting of distinct daytime and nighttime components. Notably, daytime and nighttime sleep differ with respect to a number of qualities, such as sleep bout lengths and arousal thresholds. In this short review, we describe several genetic and environmental factors that differentially affect daytime and nighttime sleep, highlighting the observations suggesting the notion that these temporally distinct components of Drosophila sleep may have unique biological functions and be regulated by different homeostatic regulatory mechanisms.